Rolandas Pavilionis and Lithiuanian Philosophy - Kabelka, Gintaras (Problemos, 2014)
This article considers the whole corpus of works of Rolandas Pavilionis in the context of Lithuanian philosophical discourse using the approach of sociology of science. Bibliometric means are applied (the measurement of the amplitude of the text, analysis of citations) to determine in quantitative terms the productivity of the philosopher, his contribution to the Lithuanian philosophy, reception of his works in Lithuania. A review is presented of the attempts of Lithuanian philosophers to interpret the philosophy of Pavilionis or to enter into polemics with it, as well as of the rising discussion, whether or not this philosopher belongs to the analytic philosophy trend. The fragmentary character of the reception of the works of this philosopher is stated here. The data presented demonstrate that Pavilionis is one of the most productive and relatively often cited philosophers in Lithuania, having written almost half of the texts of philosophy of language in Lithuania.